이동 에이전트 기반 지능형 네트워크 weather map 프레임워크 - 강현중(Hyun-Joong Kang); 남흥우(Heung-Woo Nam) (韓國컴퓨터情報學會論文誌, 2006)
Today, Internet covers a world wide range and most appliances of our life are linked to network from enterprise server to household electric appliance. Therefore, the importances of administrable framework that can grasp network state by real-time is increasing day by day. Our objective in this paper is to describe a network weather report framework that monitors network traffic and performance state to report a network situation including traffic status in real-time. We also describe a mobile agent architecture that collects state information in each network segment. The framework could inform a network manager of the network situation. Through the framework. network manager accumulates network data and increases network operating efficiency. 오늘날 네트워크는 전 세계적으로 광범위하게 퍼져있으며, 기업 서버에서부터 심지어 가정의 가전제품까지 우리 생활의 대부분의 기기들이 네트워크로 연결되는 상황에 이르렀다. 따라서 실시간으로 네트워크 상태를 파악하고 계획, 관리할 수 있는 프레임워크의 중요성이 날로 증가하고 있다. 네트워크 상황을 실시간으로 파악하고 지속적으로 최적의 상태를 유지할 수 있는 기술은 네트워크 운영의 고도화 측면에서 가장 근본적이며 핵심적인 요소이다. 고속도로 교통관제 센터의 역할과 유사하게 그물처럼 연결된 네트워크를 한눈에 파악할 수 있는 네트워크 상태보고 프레임워크가 효과적으로 구축되어 있다면 바이러스나 웜으로 인한 급격한 트래픽의 증가 또는 서비스 거부공격 등의 긴급 상황에 빠르게 대처할 수 있고, 트래픽 통계 데이터의 분석을 통해서 네트워크의 확장이나 병목구간 등을 미리 파악할 수 있을 것이다. 본 논문에서는 네트워크 트래픽과 성능 상태를 실시간으로 모니터링하고, 동적으로 보고를 해주는 네트워크 상태보고 시스템의 구조를 제시하였다. 이를 위해서 각 네트워크 세그먼트 단위에 이동성을 제공하는 지능형 에이전트를 구축하고 이를 통하여 전체 네트워크의 상태를 효과적으로 제공하는 프레임워크를 제안하였다.